Behavioral Biases in Investment: Overconfidence, Disposition Effect, and Herding Behavior - Ali, Muhammad Hasnain; Bakar, Abou; Tufail, Muhammad Sajid; Mazhar, Fatima (iRASD Journal of Economics, 2024)
This section introduces the research by outlining the importance of understanding behavioral biases in investment decisions, particularly within the context of retail investors in Pakistan. This research work primarily intends to find out the influence of behavioral biases over investors' investment decisions. The population of this research are individual investors investing in Pakistan Stock Exchange. The research design of this study is quantitative. The sample size of current research was 400 individual investors. The survey assessed several types of biases, including overconfidence, disposition effect, and herding behavior. The result outcome indicated that with an increased number of such biases present, it significantly influences the investment decisions of investors. This study specifically indicates that respondents are often subject to overconfidence, the disposition effect, and herding behavior, and finally the factors that lead to relatively poor investment decisions. These results underline the identification and need for tackling these biases within the financial decision-making domain. Financial professionals, comprising advisors and educators, are better placed with skills on how to design strategies that deter more adverse consequences of these biases. They can enhance investment quality in decision-making by well-directed training programs and advisory services. Therefore, this study underscores the pivotal role that behavioral finance plays in improving investor outcomes and calls for the rectification of behavioral bias to attain more informed and rational investment decisions.